Anatomical characteristics of the styloid process in internal carotid artery dissection: Case–control study. Issue 4 (June 2018) - Amorim, José M; Pereira, Daniela; Rodrigues, Marta G; Beato-Coelho, José; Lopes, Margarida; Cunha, André; Figueiredo, Sofia; Mendes-Pinto, Mafalda; Ferreira, Carla; Sargento-Freitas, João; Castro, Sérgio; Pinho, João
Introduction: Pathophysiology of cervical artery dissection is complex and poorly understood. In addition to well-known causative and predisposing factors, including major trauma and monogenic connective tissue disorders, morphological characteristics of the styloid process have been recently recognized as a possible risk factor for cervical internal carotid artery dissection. Aims: To study the association of the anatomical characteristics of styloid process with internal carotid artery dissection. Methods: Retrospective, multicenter, case–control study of patients with internal carotid artery dissection and age- and sex-matched controls. Consecutive patients with internal carotid artery dissection and controls with ischemic stroke or transient ischemic attack of any etiology excluding internal carotid artery dissection, who had performed computed tomography angiography, diagnosed between January 2010 and September 2016. Two independent observers measured styloid process length and styloid process distance to internal carotid artery. Results: Sixty-two patients with internal carotid artery dissection and 70 controls were included. Interobserver agreement was good for styloid process length and styloid process–internal carotid artery distance (interclass correlation coefficient = 0.89 and 0.76, respectively). Styloid process ipsilateral to dissection was longer than left and right styloid process in controls (35.8 ± 14.4 mm versus 30.4 ± 8.9 mm and 30.3 ± 8.2 mm, p = 0.011 and p = 0.008, respectively). Styloid process–internal carotid artery distance ipsilateral to dissection was shorter than left and right distance in controls (6.3 ± 1.9 mm versus 7.2 ± 2.1 mm and 7.0 ± 2.3 mm, p = 0.003 and p = 0.026, respectively). Internal carotid artery dissection was associated with styloid process length (odds ratio = 1.04 mm −1, 95% confidence interval = 1.01–1.08, p = 0.015) and styloid process–internal carotid artery distance (OR = 0.77 mm −1, 95% confidence interval = 0.64–0.92, p = 0.004). Conclusion: Longer styloid process and shorter distance between styloid process and cervical internal carotid artery are associated with cervical internal carotid artery dissection.